Automobile emissions: a problem based learning activity using the Clean Air Act - Grauer, Bette; Grauer, Diana (My University, 2013)
A problem-based learning activity has been developed using automotive engineering and requirements of the Clean Air Act to examine complex environmental issues involving automobiles. After an introductory study, students sample the O2, CO, NO, and NO2 levels of automobile exhaust and analyze the results. The activity employs a constructivist approach and is appropriate for entry-level engineering classes. It can be modified for use in upper level engineering classes as well. To prepare for the emissions analysis lab, students study the composition of atmospheric gases, products of combustion, and the measurement of automotive emissions. The laboratory component is the actual sampling of engine exhaust from student selected automobiles using an exhaust emissions analyzer. Students use sample values of emission concentrations for O2, CO, NO, and NO2, combustion kinetics, and fluid dynamics to calculate the engine fuel flow rate, exhaust flow rate, and mass emission rates for CO and NOX. This paper presents an overview of the introductory studies followed by a description of the automobile exhaust sampling activity. Representative sample data of automobile emissions are presented along with a discussion of the sampling results, a method for approximating pollutant mass emission rate levels, and comparison to EPA standards.
Keywords: Automobile emissions; Clean Air Act; Emissions; Engineering education; Problem-based learning